How research and development expenditure affects economic growth - Chiew, Yew Yi (2023)
Research and development (R&D), which fosters innovation, productivity, and competitiveness, is vital for modern economic progress. It defines the meticulous and creative work done to either produce new knowledge, products, and processes or to improve those that currently exist.This study explores whether the research and development is a better driver of economy and compares the development levels of different countries around the world and the data from 2005 to 2019. Therefore, in the new stage of promoting high-quality economic development, it is urgent to clarify the actual effect and impact mechanism of the research and development towards the country economy, deeply analyse the internal mechanism of how the research and development affects GDP growth from Research and development expenditure, researchers in researchers in research and development and patent applications. The contribution and positive and negative effects produced by the level, thus providing possible path support for how the research and development can better drive global economic growth.